Sexual behavior in hiv infected adults more than 50 years old - Bertoncini, Bruna Z; Moraes, Karla S; Kulkamp, Irene C (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: the number of aids cases is increasing in people who are at least 50 years old. HIV contamination risk in elderly adults is ignored bypart of the population and health professionals. Objective: detecting in people who are 50 years old infected by HIV virus which factors might havethe infection and verifying their sexual behavior before and after the knowledge of infection. Methods: transversal descriptive study, carried and inJanuary, 2007. The sample consisted of 50 years old people who lived in Capivari de Baixo (n = 9) and Imbituba (n = 13). The data collection wascarried through a questionnaire filled by the interviewed, constituted by closed and semiclosed questions about social, economic and cultural data,sexual behavior and knowledge about STD and HIV. Results:in this study, 21 (95,5%) subjetcts are sexually active. Half of the participants do notuse condom regularly, having a soropositive partner or not. It was observed that most people in the sample are heterosexual and have low studydegree. The main infection form was through sexual relation (72,7%), followed by injectable drugs use (27,3%). Conclusion:the HIV infection kno-wledge changed sexual behavior in half of the cases However, there is still a large resistance to condom use. We highlight the necessity of educatio-nal campaigns exclusively directed to elderly adults.